ChemInform Abstract: Remote Chirality Control Based on the Organocatalytic Asymmetric Mannich Reaction of α‐Thio Acetaldehydes. Issue 19 (13th May 2014) - Kano, Taichi; Sakamoto, Ryu; Maruoka, Keiji
Abstract Remote chirality control leading to 1, 4‐difunctionalized compounds such as 1, 4‐aminoalcohols (VII), 1, 4‐diamines (X), and 1, 4‐hydroxyalcohols (XIV) is achieved by both syn‐ and anti‐selective Mannich reactions of α‐thioacetaldehydes (I), subsequent olefination, and stereospecific 2, 3‐sigmatropic rearrangement.